OPTIMIZATION OF MCFARLAND TURBIDITY STANDARDS VALUE IN DETERMINING TEMPLATE DNA AS REFERENCE IN SALMONELLA TYPHIMURIUM ATCC 14028 TEST USING REAL-TIME PCR (QPCR) - Zulfiayu Sapiun, Alfi Sophian, Abinawanto, Muindar, Vyani Kamba, Sukmawati A. Damiti; Herman Luawo (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Background and objectives: An optimization of McFarland standards in determining the DNA template in Salmonella typhimurium ATCC 14028 test using real-time PCR (qPCR) was conducted to specify which McFarland standard value that is appropriate to be used as reference of template DNA in the particular test. Materials and Methods: Conducted in the Microbiology Laboratory of Center for Food and Drug Control (CFDC) in Gorontalo, this research relied on qualitative analysis using real-time PCR with SYBR Green method. Moreover, DNA isolation technique involved direct method by extracting one ose needle from Nutrient Agar (NA) slant medium. Further, the data analysis was conducted in two steps: 1) amplification of DNA template and observation of cycle threshold (Ct) and melting temperature (Tm) values; 2) statistical analysis by one-way ANOVA. Results: The results indicate that the average Ct value is in 15.18 - 15.53. Statistical analysis on Ct value indicates Fcount < Ftable, (or 0.109 < F critical 1.541) with ? = 0.05; signifying that McFarland turbidity standard value does not influence the Ct value. Further, as the result of Tm analysis indicates, the average value of Tm is in 84.8 - 85.7. Statistical analysis on Tm value indicates Fcount < Ftable, (or 0.281 < F critical 1.541) with ? = 0.05; signifying that McFarland turbidity standard value does not influence the Tm value. Conclusion: All in all, this research concludes that the reference template DNA for qPCR analysis by McFarland turbidity standard is 0.5 - 2.